1997
DOI: 10.1007/s004250050072
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-transform infrared and Raman spectroscopic evidence for the incorporation of cinnamaldehydes into the lignin of transgenic tobacco (Nicotiana tabacum L.) plants with reduced expression of cinnamyl alcohol dehydrogenase

Abstract: Xylem from stems of genetically manipulated tobacco plants which had had cinnamyl alcohol dehydrogenase (CAD; EC 1.1.1.195) activity down-regulated to a greater or lesser degree (clones 37 and 49, respectively) by the insertion of antisense CAD cDNA had similar, or slightly higher, lignin contents than xylem from wild-type plants. Fourier-transform infrared (FT-IR) microspectroscopy indicated that down-regulation of CAD had resulted in the incorporation of moieties with conjugated carbonyl groups into lignin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 34 publications
(39 reference statements)
9
102
0
1
Order By: Relevance
“…The value of A 1510 of the bm1 mutant is con-siderably lower compared with the wild type and bm1 heterozygote and there is a statistically significant difference between genotypes (P = 0.0007). A high ratio of A 1665 : A 1510 and A 1595 : A 1510 is indicative of the incorporation of coniferaldehyde residues in the cell wall (Mackay et al, 1997;Stewart et al, 1997). Both ratios are higher in the bm1 mutant, confirming the results from Wiesner reactions (Figure 2).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The value of A 1510 of the bm1 mutant is con-siderably lower compared with the wild type and bm1 heterozygote and there is a statistically significant difference between genotypes (P = 0.0007). A high ratio of A 1665 : A 1510 and A 1595 : A 1510 is indicative of the incorporation of coniferaldehyde residues in the cell wall (Mackay et al, 1997;Stewart et al, 1997). Both ratios are higher in the bm1 mutant, confirming the results from Wiesner reactions (Figure 2).…”
Section: Resultssupporting
confidence: 76%
“…The peak at 1665 cm −1 represents C=O stretching in the carbonyl moiety of conjugated aldehydes or ketones (Mackay et al, 1997;Stewart et al, 1997) and based on an ANOVA the difference in absorbance that is observed for the three genotypes is statistically significant (P = 0.0004). The peaks at 1595 and 1510 cm −1 are indicative of lignin and hydroxycinnamic acids (Stewart et al, 1997). The value of A 1510 of the bm1 mutant is con-siderably lower compared with the wild type and bm1 heterozygote and there is a statistically significant difference between genotypes (P = 0.0007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, the molecular approach has primarily been devoted to attempts at determining the effects of differentially expressing genes encoding putative regulatory enzymes in the lignin biosynthetic pathway (Figure 3) (56)(57)(58)(59)(60)(61)(62). As can be seen, there are essentially only four types of transformations beyond cinnamic acid, namely aromatic hydroxylations (63)(64)(65), O-methylations (66-68), CoA ligations and (consecutive) NADPH dependent reductions (69).…”
Section: Phenylpropanoid Metabolic Flux: Its Modulation and Controlmentioning
confidence: 99%